Recreational activities performed with neoplasia carrier Inpatients in a general hospital - Caroline de Castro Moura; Zélia Marilda Rodrigues Resck; Eliza Maria Rezende Dázio (Universidade Federal do Ceará, 2012)
This study aims at apprehending the contribution of recreational activities in the treatment of hospitalized cancer patients and identifying the most stimulating resources for them. This is a qualitative research of phenomenological nature, it was approved by the Ethics in Research Committee, Protocol 139/2010. It was conducted with patients with cancer in a general hospital, located in Alfenas, in March and April, 2011.The research began from these guiding questions: What are your thoughts on the recreational team work and the activities they do? What do you suggest for this group to be developed? It was perceived that ludic activities help patients to face the disease, that they eased the interaction between the recreational group and the multiprofessional team, besides providing a happy and welcoming environment. The most well accepted activities were music and games the clowns provided. We suggest implementing the humanization by using ludic resources.